An Analysis of the Violation of Maxims In Youtube Channel Jeda Nulis - Aziz Maulana (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
The aim of thi study to determine the types of maxims contained in the Youtube Channel video "Jeda Nulis" by the title “ Pengalaman Jadi Santri Islam dan Seminaris Katholik” and to find out the intended meanings implied on violated maxims. This study uses a qualitative descriptive method. In collecting data, this study use documenting the data. The first step is to transcribe and translating the video and then group various maxims into certain categories and then analyze the meaning of the pronunciation of the maxims. The writer finds five quotes that include the maxims of both the interviewer and the informant. The interviewer violated a maximum of 3 times while the interviewee committed a violation 2 times. From the interviewer and resource person's conversation, it was found that there were two violations of the maxim of quantity, one violation of the maxim of quality, two violations of the maxim of relevance, and zero violations of the maxim of manner. The following is an explanation of the data that has been found. And in the video, there is no violation of Manner. Because in conversations involving religion, of course the speaker must be wise in sorting words so that they are very clear and unbiased. Because if a conversation becomes ambiguous, it will be very dangerous and cause negative perspectives for others who hear it.